The study of environment-conscious attitudes in the food-industry companies of the Northern-Plain Region - Odor, Kinga (Acta Agraria Debreceniensis, 2008)
that the world of business, profit and work is not a hermetically closed area, but is in interaction with its closer and wider surroundings, ultimately with society and the natural environment.The affectedness of each sector and company varies. To be able to tackle these problems, first and foremost the commitment of companies towards environmentally conscious attitude is necessary, which can form as a result of inner obligation or outer pressure. Thus companies will be concerned to measure and quantify the environmental effects of all activities.Some of the companies have already given their votes for environment-protection. Both internationally and at home it seems that the responsible leaders of more and more companies build social, human rights and environmental protection considerations in the objects and values of the company apart from profit maximization.In my thesis I present the data gathered from a questionnaire survey carried out with food-industry companies in the Northern-Plain Region. The aim of the survey was to evaluate the commitment of companies towards environmental protection via solid data. The fact that more than half of the respondents found the positive effects of environmental protection of little importance and that environmental protection was the last among the aims of some companies reflected greatly in the following outcomes.